LY2874455 and Abemaciclib Reverse FGF3/4/19/CCND1 Amplification Mediated Gefitinib Resistance in NSCLC - Liu, Dongcheng; Liu, Hongguang; Gan, Jiadi; Zeng, Shinuan; Zhong, Fuhua; Zhang, Bin; Zhang, Zhe; Zhang, Siyu; Jiang, Lu; Wang, Guangsuo; Chen, Yixin; Kong, Feng-Ming Spring; et al. (Frontiers in Pharmacology, 2022)
Non-small cell lung carcinoma (NSCLC) patients who initially received TKI therapy often acquired resistance via multiple complex mechanisms. The amplification of FGF3/4/19/CCND1 on chromosome 11q13 was found in many cancers with TKI resistance. However, the role of these amplification in TKI-resistant NSCLC remains uncovered. Here, we generated FGF3/4/19/CCND1 amplification model in the NSCLC cell lines PC-9 and HCC827. Upregulation of FGF3/4/19/CCND1 strongly promoted cell proliferation and gefitinib resistance in NSCLC cells. To find out the potential therapeutic strategies, we screened the combination of inhibitors against FGF/FGFR signaling pathway and CCND1/CDK4 complex and revealed that gefitinib combined with LY2874455 and abemaciclib exhibited the most effective inhibition of resistance in vitro and in vivo. Mechanistically, FGFs/CCND1 activated MAPK pathway which was abolished by the combination drugs. Our study provides a rationale for clinical testing of dual targeting FGFR and CCND1 with LY2874455 and abemaciclib in NSCLC patients who harbored FGF3/4/19/CCND1 amplification.